A model of internal firm relocation in the Netherlands - Corina Huisman; Leo JG Van Wissen (European Regional Science Association (ERSA), 2005)
This paper presents a model of internal relocation of firms in the Netherlands. Firm relocation is driven both by firm internal factors, such as growth, age, and type of activity, as well as external factors, relating to the business cycle, the geographical environment, the composition of the labour force, and the composition of the firm popuation, as well as linkages with other firms. Using a unique longitudinal database of firms in the Province of Gelderland in the Netherlands, we specify and estimate two related models of firm relocation. The decomposition of the migration process in two subprocesses is consitent with the theory of a two stage decision process, whereby in th first stage the firm decides to move, and in the second step it chooses an alternative destination. Different factors are important in both stages of the process.
Keywords: 330